ARE OUR PEOPLE HEALTH CONSCIOUS? RESULTS OF A PATIENTS SURVEY IN KARACHI, PAKISTAN - Qidwai, Waris; Saleheen, Danish; Saleem, Sadia; Andrades, Marie; Azam, Syed Iqbal (Journal of Ayub Medical College Abbottabad, 2003)
Background: Life style is known to influence health and may be responsible for certain diseases. There is a need to document the life style on health among the Pakistani population. Methods: The study was conducted on patients visiting the Family Practice Center, the Aga Khan University, Karachi. A questionnaire was used to collect information on the demographic profile, and the life style on health. The ethical requirements for conducting the study were met. Results: 393 patients were surveyed. The majority were young married men, in either private or government service. Preference for consumption of fats/oils, sweets, spicy foods, salt, fruits/ vegetables, tea, coffee, cola drinks and alcohol was found among 103 (26%), 84 (22%), 86 (22%), 110 (28%), 239 (61%), 319 (81%), 117 (30%), 253 (64%) and 13 (03%) respondents respectively. Hand washing after defecation, before eating food and after work was seen among 341 (87%), 296 (75%) and 256 (65%) respondents respectively. Brushing of teeth after eating food, before breakfast and bedtime was seen in 56 (14%), 346 (88%) and 176 (45%) respondents respectively. Preventive dental check-up was practiced by 102 (26%) of the respondents. Sleep of less than 6 hours per day among 74 (19%), water consumption of less than 1 liter daily among 84 (21%) and fish consumption on once a week basis among 173 (44%) respondents was found. Tobacco and betel nuts use was found among 69 (17%) and 79 (20%) respondents. Conclusions: We have documented a clear need to raise public awareness on the issue of life style on health. There is a need and we strongly recommend debate and further research, along with interventional strategies in line with the available evidence on healthy life style. Key-words: Health behavior, Life style, Physical fitness, Diet